Champā : History and Culture of an Indian Colonial Kingdom in the Far East 2nd-16th Century A.D. - Majumdar, R.C., (Brill | Manohar Publishers & Distributors, 2024)
Champā is a former name of the independent Cham polities that extended across the coast of present-day central and southern Vietnam from approximately second century AD till 1832. This book covers the history of Champā region by covering the developments in the political and religious histories. This book contains the description of the foundation of Champā kingdom, and contains details of various Hindu kingdoms and the histories of Gangaraja, Panduranga and Bhrigu dynasties. It also contains the details of invasion of Champā region by the Annams, Cambodians, and Mongols, followed by the state system adopted in Champā region. The latter half of the book deals with the religious history of Champā, where it covers Buddhism, Shaivism, Vaishnavaism, and other minor Hindu sects, and also discusses the archaeological structures associated with the religious sites.